A Ce-Co-Mo / TiO2 denitrification catalyst with a wide temperature window, high water and sulfur resistance, and a preparation method thereof
By precipitating cerium elements on the titanium dioxide support and introducing cobalt and molybdenum elements through the impregnation method, Ce-Co-Mo/TiO2 catalyst was prepared, which solved the problem of narrow temperature window of vanadium tungsten catalyst and poor water and sulfur resistance, and achieved a denitrogenation catalyst with wide temperature window and high water and sulfur resistance.
Patent Information
- Application Number
- CN202411859761.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, vanadium tungsten catalysts have problems such as narrow temperature window and poor water and sulfur resistance during the denitrification process, which leads to the denitrition efficiency of the catalyst when water and sulfur dioxide exist in the flue gas, and can cause potential harm to the environment and health.
The Ce-Co-Mo/TiO2 catalyst was used to support the cerium element onto the titanium dioxide support by precipitation method, and cobalt and molybdenum elements were introduced by impregnation method to form a catalyst with a wide temperature window and high water and sulfur resistance.
The wide temperature window design of the catalyst is realized, ensuring efficient denitrification performance under different temperature conditions, and has strong water and sulfur resistance, avoiding environmental and health hazards.
Smart Images

Figure CN119733524A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst materials, and more particularly to a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance and a preparation method thereof. Background Art
[0002] Nitrogen oxides NO x Considered as a classic air pollutant, the main sources of nitrogen oxide emissions include industrial production, transportation, coal-fired power generation, agricultural activities, etc. These emission sources will release nitrogen oxides into the atmosphere, causing negative impacts on air quality and the environment, and threatening human health. In order to avoid the pollution of nitrogen oxides to the atmosphere, NH3 selective catalytic reduction of NO x The technology has been widely used in the purification of industrial flue gas and tail gas. Although the polymer catalytic reduction technology has a high conversion rate, it also has problems such as high cost and immature technology.
[0003] Although the catalyst-free selective reduction technology has low cost, it has low conversion rate, unstable conversion efficiency, and cannot meet emission standards. Although polymer catalytic reduction technology has a high conversion rate, it also has problems such as high cost and immature technology. Nowadays, most catalysts used in selective catalytic reduction technology are vanadium tungsten catalysts, but during the reaction process, vanadium tungsten catalysts will pollute the environment and cause certain harm to people's health. The temperature window of vanadium tungsten catalysts is narrow, and the expected denitrification efficiency cannot be achieved in a certain temperature range. Water and sulfur dioxide are often present in the flue gas duct, which will reduce the denitrification efficiency of the catalyst when using vanadium tungsten catalysts. This is because vanadium tungsten catalysts have poor sulfur resistance.
[0004] Therefore, how to develop a Ce-Co-Mo / TiO2 denitrification catalyst with a wide temperature window, high water and sulfur resistance, and a preparation method thereof for exhaust gas treatment to promote the conversion of nitrogen oxides in exhaust gas to generate more nitrogen and water is an urgent problem that technicians in this field need to solve. Summary of the invention
[0005] In view of this, the present invention provides a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window, high water resistance and high sulfur resistance, and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance, comprising the following steps:
[0008] (1) adding cerium nitrate hexahydrate to deionized water, dissolving it by ultrasonication, and then stirring it, and then adding titanium dioxide powder, and magnetically stirring it at room temperature to obtain a solution;
[0009] (2) adding NH3·H2O dropwise to the obtained solution to adjust the pH to 9, continuing stirring, then separating the solid from the liquid, washing the solid with deionized water until it is neutral, drying, and calcining to obtain a Ce / TiO2 catalyst;
[0010] (3) Grind the obtained Ce / TiO2 catalyst into powder for later use, add cobalt nitrate hexahydrate and ammonium heptamolybdate tetrahydrate into deionized water, ultrasonically dissolve them, and then stir to obtain a solution, add Ce / TiO2 catalyst powder into the solution, add deionized water and stir, then put it into a water bath and stir, dry, and calcine to obtain the wide temperature window, high water and sulfur resistance denitration catalyst Ce-Co-Mo / TiO2.
[0011] Beneficial effects of the present invention: The present invention uses a precipitation method to load cerium onto a titanium dioxide carrier, and then uses an impregnation method to load cobalt and molybdenum into the catalyst after treating the titanium dioxide carrier. The final test results show that both cobalt and molybdenum are successfully introduced into the catalyst surface, and water and sulfur resistance tests are performed at the same time. The catalyst prepared by the method of the present invention has a wide temperature window, does not cause harm to the environment, and has strong water and sulfur resistance.
[0012] Furthermore, in step (1), the addition ratio of cerium nitrate hexahydrate, titanium dioxide powder and deionized water is: 0.2523-1.2614 g cerium nitrate hexahydrate and 5 g titanium dioxide powder are added per 100 mL deionized water.
[0013] Furthermore, in step (1), the titanium dioxide powder is anatase titanium dioxide powder with a particle size of 5-10 nm.
[0014] Furthermore, in step (1), cerium nitrate hexahydrate is added to deionized water for ultrasonic dissolution, the ultrasonic power is 80W, the ultrasonic time is 10min, and then stirred, the stirring speed is 500rpm, and the stirring time is 20min.
[0015] Furthermore, in step (1), titanium dioxide powder was added and magnetic stirring was performed at room temperature with a stirring speed of 500 rpm and a stirring time of 1 h.
[0016] Furthermore, in step (2), stirring was continued for 4 h at a stirring speed of 500 rpm.
[0017] Furthermore, in step (2), the drying temperature is 80°C, the drying time is 12h, and the calcination step is: heating from room temperature to 500°C at a heating rate of 5°C / min, and keeping warm for 4h.
[0018] Furthermore, in step (3), the addition ratio of cobalt nitrate hexahydrate, ammonium heptamolybdate tetrahydrate, Ce / TiO2 catalyst powder and deionized water is: 0.2536g of cobalt nitrate hexahydrate, 0.5129-1.5386g of ammonium heptamolybdate tetrahydrate, and 5g of Ce / TiO2 catalyst powder are added per 100mL of deionized water, and the volume ratio of the two additions of deionized water is 1:1.
[0019] Further, in step (3), cobalt nitrate hexahydrate and ammonium heptamolybdate tetrahydrate are added to deionized water for ultrasonic dissolution, the ultrasonic power is 80W, the ultrasonic time is 10min, and then stirred for 20min at a stirring speed of 500rpm. Ce / TiO2 catalyst powder is put into the solution, and deionized water is added and stirred at a stirring speed of 500rpm for 30min. The solution is put into a 80°C water bath and stirred at a stirring speed of 500rpm for 4h. The drying temperature is 80°C and the drying time is 12h. The calcination step is as follows: heating from room temperature to 500°C at a heating rate of 5°C / min and keeping warm for 4h.
[0020] The present invention also provides a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance prepared by the above method.
[0021] Beneficial effects of the present invention: The catalyst Ce-Co-Mo / TiO2 of the present invention has a wide temperature window, does not cause harm to the environment, has strong water and sulfur resistance, is used for tail gas treatment, and promotes the conversion rate of nitrogen oxides in the tail gas to generate more nitrogen and water. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 To explore the effect of different ratios of single cerium catalysts in Examples 1-5 on NO conversion rate;
[0023] Figure 2 The effects of different ratios of cerium-cobalt catalysts in Example 1 and Comparative Examples 1-6 on NO conversion were explored;
[0024] Figure 3 is the NO conversion rate of the catalysts of Comparative Example 1 Ce- / TiO2, Comparative Example 3 Ce-Co / TiO2, Comparative Example 7 Co-Mo / TiO2, and Example 6 Ce-Co-Mo / TiO2;
[0025] Figure 4 Examples 6-8 compare different ratios of Ce-Co-Mo x / NO conversion rate of TiO2 catalyst;
[0026] Figure 5 The purpose is to compare the NO conversion rate of Ce-Co-Mo2 / TiO2 catalyst with water and without water in Example 6;
[0027] Figure 6 The water and sulfur resistance of the catalysts of Comparative Example 1 Ce- / TiO2, Comparative Example 3 Ce-Co / TiO2, and Example 6 Ce-Co-Mo2 / TiO2 are shown. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] The preparation method of Ce / TiO2 catalyst comprises the following steps:
[0031] (1) 1.2614 g of cerium nitrate hexahydrate was added to 100 mL of deionized water and ultrasonically dissolved at an ultrasonic power of 80 W for 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0032] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH value to 9, and stirring was continued for 4 hours at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral. The solid was dried in an oven at a drying temperature of 80°C for a drying time of 12 hours, and calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C, and kept at this temperature for 4 hours to obtain a yCe / TiO2 catalyst, where y=Ce / Ti molar ratio, y=10, recorded as 10Ce / TiO2.
[0033] Example 2
[0034] The preparation method of Ce / TiO2 catalyst comprises the following steps:
[0035] (1) 0.2523 g of cerium nitrate hexahydrate was added to 100 mL of deionized water and ultrasonically dissolved at an ultrasonic power of 80 W for 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0036] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH value to 9, and stirring was continued for 4 hours at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral. The solid was dried in an oven at a drying temperature of 80°C for a drying time of 12 hours, and calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C, and kept at this temperature for 4 hours to obtain a yCe / TiO2 catalyst, where the molar ratio of y=Ce / Ti, y=2, was recorded as 2Ce / TiO2.
[0037] Example 3
[0038] The preparation method of Ce / TiO2 catalyst comprises the following steps:
[0039] (1) 0.5046 g of cerium nitrate hexahydrate was added to 100 mL of deionized water and ultrasonically dissolved at an ultrasonic power of 80 W for 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0040] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH value to 9, and stirring was continued for 4 hours at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral. The solid was dried in an oven at a drying temperature of 80°C for a drying time of 12 hours, and calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C, and kept at this temperature for 4 hours to obtain a yCe / TiO2 catalyst, where the molar ratio of y=Ce / Ti, y=4, was recorded as 4Ce / TiO2.
[0041] Example 4
[0042] The preparation method of Ce / TiO2 catalyst comprises the following steps:
[0043] (1) 0.7568 g of cerium nitrate hexahydrate was added to 100 mL of deionized water and ultrasonically dissolved at an ultrasonic power of 80 W for 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0044] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH value to 9, and stirring was continued for 4 hours at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral. The solid was dried in an oven at a drying temperature of 80°C for a drying time of 12 hours, and calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C, and kept at this temperature for 4 hours to obtain a yCe / TiO2 catalyst, where the molar ratio of y=Ce / Ti, y=6, was recorded as 6Ce / TiO2.
[0045] Example 5
[0046] The preparation method of Ce / TiO2 catalyst comprises the following steps:
[0047] (1) 1.0091 g of cerium nitrate hexahydrate was added to 100 mL of deionized water and ultrasonically dissolved at an ultrasonic power of 80 W for 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0048] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH value to 9, and stirring was continued for 4 hours at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral. The solid was dried in an oven at a drying temperature of 80°C for a drying time of 12 hours, and calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C, and kept at this temperature for 4 hours to obtain a yCe / TiO2 catalyst, where the molar ratio of y=Ce / Ti, y=8, was recorded as 8Ce / TiO2.
[0049] Example 6
[0050] A method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance comprises the following steps:
[0051] The Ce / TiO2 catalyst obtained in Example 1 was ground into powder for later use. 0.2536 g of cobalt nitrate hexahydrate and 1.0257 g of ammonium heptamolybdate tetrahydrate were added to 50 mL of deionized water for ultrasonic dissolution at an ultrasonic power of 80 W for 10 min, and then stirred for 20 min at a stirring speed of 500 rpm to obtain a solution. 5 g of Ce / TiO2 catalyst powder was put into the solution, and 50 mL of deionized water was added and stirred at a stirring speed of 500 rpm for 30 min. The solution was then placed in a 80°C water bath and stirred at a stirring speed of 500 rpm for 4 h. The solution was dried in an oven at a drying temperature of 80°C for 12 h. The solution was calcined in a muffle furnace and heated from room temperature to 500°C at a heating rate of 5°C / min and kept warm for 4 h to obtain Ce-Co-Mox / TiO2, x=molar ratio of Mo / Ce, x=2, recorded as Ce-Co-Mo2 / TiO2.
[0052] Example 7
[0053] A method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance comprises the following steps:
[0054] The Ce / TiO2 catalyst obtained in Example 1 was ground into powder for later use. 0.2536 g of cobalt nitrate hexahydrate and 0.5129 g of ammonium heptamolybdate tetrahydrate were added to 50 mL of deionized water for ultrasonic dissolution at an ultrasonic power of 80 W for 10 min, and then stirred for 20 min at a stirring speed of 500 rpm to obtain a solution. 5 g of Ce / TiO2 catalyst powder was put into the solution, and 50 mL of deionized water was added and stirred at a stirring speed of 500 rpm for 30 min. The solution was then placed in a 80°C water bath and stirred at a stirring speed of 500 rpm for 4 h. The solution was dried in an oven at a drying temperature of 80°C for 12 h. The solution was calcined in a muffle furnace and heated from room temperature to 500°C at a heating rate of 5°C / min and kept warm for 4 h to obtain Ce-Co-Mo x / TiO2, x=the molar ratio of Mo / Ce, x=1, recorded as Ce-Co-Mo1 / TiO2.
[0055] Example 8
[0056] A method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance comprises the following steps:
[0057] The Ce / TiO2 catalyst obtained in Example 1 was ground into powder for later use. 0.2536 g of cobalt nitrate hexahydrate and 1.5386 g of ammonium heptamolybdate tetrahydrate were added to 50 mL of deionized water for ultrasonic dissolution at an ultrasonic power of 80 W for 10 min, and then stirred for 20 min at a stirring speed of 500 rpm to obtain a solution. 5 g of Ce / TiO2 catalyst powder was put into the solution, and 50 mL of deionized water was added and stirred at a stirring speed of 500 rpm for 30 min. The solution was then placed in a 80°C water bath and stirred at a stirring speed of 500 rpm for 4 h. The solution was dried in an oven at a drying temperature of 80°C for 12 h. The solution was calcined in a muffle furnace and heated from room temperature to 500°C at a heating rate of 5°C / min and kept warm for 4 h to obtain Ce-Co-Mo x / TiO2, x=the molar ratio of Mo / Ce, x=3, recorded as Ce-Co-Mo3 / TiO2.
[0058] Comparative Example 1
[0059] The preparation method of Co / TiO2 comprises the following steps:
[0060] (1) 0.2536 g of cobalt nitrate hexahydrate was added to 100 mL of deionized water and ultrasonically dissolved at an ultrasonic power of 80 W for 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0061] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH value to 9, and stirring was continued for 4 hours at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral. The solid was dried in an oven at a drying temperature of 80°C for a drying time of 12 hours, and calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C, and kept at this temperature for 4 hours to obtain Co / TiO2.
[0062] Comparative Example 2
[0063] The preparation method of Ce-Co / TiO2 comprises the following steps:
[0064] The Ce / TiO2 catalyst obtained in Example 1 was ground into powder for later use. 0.0845 g of cobalt nitrate hexahydrate was added to 50 mL of deionized water for ultrasonic dissolution at an ultrasonic power of 80 W for 10 min, and then stirred for 20 min at a stirring speed of 500 rpm to obtain a solution. 5 g of Ce / TiO2 catalyst powder was put into the solution, and 50 mL of deionized water was added and stirred at a stirring speed of 500 rpm for 30 min. The solution was then placed in an 80°C water bath and stirred at a stirring speed of 500 rpm for 4 h. The solution was then dried in an oven at a drying temperature of 80°C for 12 h. The solution was then calcined in a muffle furnace, and the temperature was raised from room temperature to 500°C at a heating rate of 5°C / min, and kept warm for 4 h to obtain Ce-Co z / TiO2, z = Co / Ce molar ratio, z = 0.1, recorded as Ce-Co 0.1 / TiO2.
[0065] Comparative Example 3
[0066] The preparation method of Ce-Co / TiO2 comprises the following steps:
[0067] The Ce / TiO2 catalyst obtained in Example 1 was ground into powder for later use. 0.2536 g of cobalt nitrate hexahydrate was added to 50 mL of deionized water for ultrasonic dissolution at an ultrasonic power of 80 W for 10 min, and then stirred for 20 min at a stirring speed of 500 rpm to obtain a solution. 5 g of Ce / TiO2 catalyst powder was put into the solution, and 50 mL of deionized water was added and stirred at a stirring speed of 500 rpm for 30 min. The solution was then placed in a 80°C water bath and stirred at a stirring speed of 500 rpm for 4 h. The solution was then dried in an oven at a drying temperature of 80°C for 12 h. The solution was then calcined in a muffle furnace, heated from room temperature to 500°C at a heating rate of 5°C / min, and kept warm for 4 h to obtain Ce-Co z / TiO2, z = Co / Ce molar ratio, z = 0.3, recorded as Ce-Co 0.3 / TiO2.
[0068] Comparative Example 4
[0069] The preparation method of Ce-Co / TiO2 comprises the following steps:
[0070] The Ce / TiO2 catalyst obtained in Example 1 was ground into powder for later use. 0.4227 g of cobalt nitrate hexahydrate was added to 50 mL of deionized water for ultrasonic dissolution at an ultrasonic power of 80 W for 10 min, and then stirred for 20 min at a stirring speed of 500 rpm to obtain a solution. 5 g of Ce / TiO2 catalyst powder was put into the solution, and 50 mL of deionized water was added and stirred at a stirring speed of 500 rpm for 30 min. The solution was then placed in a 80°C water bath and stirred at a stirring speed of 500 rpm for 4 h. The solution was then dried in an oven at a drying temperature of 80°C for 12 h. The solution was then calcined in a muffle furnace, heated from room temperature to 500°C at a heating rate of 5°C / min, and kept warm for 4 h to obtain Ce-Co z / TiO2, z = Co / Ce molar ratio, z = 0.5, recorded as Ce-Co 0.5 / TiO2.
[0071] Comparative Example 5
[0072] The preparation method of Ce-Co / TiO2 comprises the following steps:
[0073] The Ce / TiO2 catalyst obtained in Example 1 was ground into powder for later use. 0.5918 g of cobalt nitrate hexahydrate was added to 50 mL of deionized water for ultrasonic dissolution at an ultrasonic power of 80 W for 10 min, and then stirred for 20 min at a stirring speed of 500 rpm to obtain a solution. 5 g of Ce / TiO2 catalyst powder was put into the solution, and 50 mL of deionized water was added and stirred at a stirring speed of 500 rpm for 30 min. The solution was then placed in an 80°C water bath and stirred at a stirring speed of 500 rpm for 4 h. The solution was then dried in an oven at a drying temperature of 80°C for 12 h. The solution was then calcined in a muffle furnace, and the temperature was raised from room temperature to 500°C at a heating rate of 5°C / min, and kept warm for 4 h to obtain Ce-Co z / TiO2, z = Co / Ce molar ratio, z = 0.7, recorded as Ce-Co 0.7 / TiO2.
[0074] Comparative Example 6
[0075] The preparation method of Ce-Co / TiO2 comprises the following steps:
[0076] The Ce / TiO2 catalyst obtained in Example 1 was ground into powder for later use. 0.7609 g of cobalt nitrate hexahydrate was added to 50 mL of deionized water for ultrasonic dissolution at an ultrasonic power of 80 W for 10 min, and then stirred for 20 min at a stirring speed of 500 rpm to obtain a solution. 5 g of Ce / TiO2 catalyst powder was put into the solution, and 50 mL of deionized water was added and stirred at a stirring speed of 500 rpm for 30 min. The solution was then placed in a 80°C water bath and stirred at a stirring speed of 500 rpm for 4 h. The solution was then dried in an oven at a drying temperature of 80°C for 12 h. The solution was then calcined in a muffle furnace, heated from room temperature to 500°C at a heating rate of 5°C / min, and kept warm for 4 h to obtain Ce-Co z / TiO2, z = Co / Ce molar ratio, z = 0.9, recorded as Ce-Co 0.9 / TiO2.
[0077] Comparative Example 7
[0078] The preparation method of Co-Mo / TiO2 comprises the following steps:
[0079] (1) 0.2536 g of cobalt nitrate hexahydrate and 1.0257 g of ammonium heptamolybdate tetrahydrate were added to 100 mL of deionized water for ultrasonic dissolution, with an ultrasonic power of 80 W and an ultrasonic time of 10 min, followed by stirring at a stirring speed of 500 rpm for 20 min, and then 5 g of anatase titanium dioxide powder with a particle size of 5-10 nm was added, and magnetic stirring was performed at room temperature at a stirring speed of 500 rpm for 1 h to obtain a solution;
[0080] (2) NH3·H2O was added dropwise to the obtained solution to adjust the pH value to 9, and stirring was continued for 4 hours at a stirring speed of 500 rpm. Then, the solid was separated from the liquid, and the solid was washed with deionized water until it was neutral. The solid was dried in an oven at a drying temperature of 80°C for a drying time of 12 hours, and calcined in a muffle furnace at a heating rate of 5°C / min from room temperature to 500°C, and kept at this temperature for 4 hours to obtain Co-Mo / TiO2.
[0081] The products of the examples and comparative examples were ground into 40-60 mesh particles for testing.
[0082] Figure 1 The effects of different ratios of single cerium catalysts in Examples 1-5 on the NO conversion rate were investigated, and the optimal catalyst was 10Ce / TiO2, T 90 =310~425℃.
[0083] Figure 2 The effects of different ratios of cerium-cobalt catalysts on NO conversion were investigated in Example 1 and Comparative Examples 1-6. The optimal catalyst was Ce-Co 0.3 / TiO2, T 90 =225~350℃.
[0084] Figure 3 The NO conversion rates of Ce- / TiO2 in Comparative Example 1, Ce-Co / TiO2 in Comparative Example 3, Co-Mo / TiO2 in Comparative Example 7, and Ce-Co-Mo / TiO2 in Example 6 are shown in Table 1. The results show that the temperature window of Ce-Co-Mo / TiO2 catalyst is the widest and the optimal T 90 =225~410℃.
[0085] Figure 4 Examples 6-8 compare different ratios of Ce-Co-Mo x / TiO2 catalyst has the widest temperature window and the best T 90 =225~410℃.
[0086] Figure 5 The NO conversion rate of Ce-Co-Mo2 / TiO2 catalyst with water added and without water in Example 6 was compared. The results showed that H2O promoted the catalyst, the temperature window moved to the right and the conversion rate remained above 90%.
[0087] Figure 6The water and sulfur resistance of the Ce- / TiO2 catalysts in comparative example 1, comparative example 3, and example 6 Ce-Co-Mo2 / TiO2 are shown. The results show that under the conditions of 270°C + 5% H2O + 50ppm SO2, the water and sulfur resistance of the Ce-Co-Mo2 / TiO2 catalyst remained above 95% and did not decrease, while the activity of the Ce / TiO2 catalyst dropped to below 30%, and the activity of the Ce-Co / TiO2 catalyst dropped to more than 70%.
[0088] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance, characterized in that: The steps include: (1) adding cerium nitrate hexahydrate to deionized water, dissolving it by ultrasonication, and then stirring it, and then adding titanium dioxide powder, and magnetically stirring it at room temperature to obtain a solution; (2) adding NH3·H2O dropwise to the obtained solution to adjust the pH to 9, continuing stirring, then separating the solid from the liquid, washing the solid with deionized water until it is neutral, drying, and calcining to obtain a Ce / TiO2 catalyst; (3) Grind the obtained Ce / TiO2 catalyst into powder for later use, add cobalt nitrate hexahydrate and ammonium heptamolybdate tetrahydrate into deionized water, ultrasonically dissolve them, and then stir to obtain a solution, add Ce / TiO2 catalyst powder into the solution, add deionized water and stir, then put it into a water bath and stir, dry, and calcine to obtain the wide temperature window, high water and sulfur resistance denitration catalyst Ce-Co-Mo / TiO2.
2. The method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance according to claim 1, characterized in that: In step (1), the addition ratio of cerium nitrate hexahydrate, titanium dioxide powder and deionized water is: 0.2523-1.2614 g cerium nitrate hexahydrate and 5 g titanium dioxide powder are added to every 100 mL deionized water.
3. The method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance according to claim 1, characterized in that: In step (1), the titanium dioxide powder is anatase titanium dioxide powder with a particle size of 5-10 nm.
4. The method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance according to claim 1, characterized in that: In step (1), cerium nitrate hexahydrate is added to deionized water and ultrasonically dissolved, the ultrasonic power is 80W, the ultrasonic time is 10min, and then stirred, the stirring speed is 500rpm, and the stirring time is 20min.
5. The method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance according to claim 1, characterized in that: In step (1), titanium dioxide powder was added and magnetic stirring was performed at room temperature with a stirring speed of 500 rpm and a stirring time of 1 h.
6. The method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance according to claim 1, characterized in that: In step (2), stirring was continued for 4 h at a stirring speed of 500 rpm.
7. The method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance according to claim 1, characterized in that: In step (2), the drying temperature is 80° C. and the drying time is 12 h. The calcination step is: heating from room temperature to 500° C. at a heating rate of 5° C. / min and keeping the temperature for 4 h.
8. The method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance according to claim 1, characterized in that: In step (3), the addition ratio of cobalt nitrate hexahydrate, ammonium heptamolybdate tetrahydrate, Ce / TiO2 catalyst powder and deionized water is: 0.2536g of cobalt nitrate hexahydrate, 0.5129-1.5386g of ammonium heptamolybdate tetrahydrate, and 5g of Ce / TiO2 catalyst powder are added per 100mL of deionized water, and the volume ratio of the two additions of deionized water is 1:
1.
9. The method for preparing a Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance according to claim 1, characterized in that: In step (3), cobalt nitrate hexahydrate and ammonium heptamolybdate tetrahydrate are added to deionized water for ultrasonic dissolution, the ultrasonic power is 80W, the ultrasonic time is 10min, and then stirred for 20min at a stirring speed of 500rpm. Ce / TiO2 catalyst powder is put into the solution, and deionized water is added and stirred at a stirring speed of 500rpm for 30min. The solution is put into a 80°C water bath and stirred at a stirring speed of 500rpm for 4h. The drying temperature is 80°C and the drying time is 12h. The calcination step is as follows: heating from room temperature to 500°C at a heating rate of 5°C / min and keeping warm for 4h.
10. A Ce-Co-Mo / TiO2 denitration catalyst with a wide temperature window and high water and sulfur resistance prepared by the method according to any one of claims 1 to 9.